2022
DOI: 10.12890/2022_003477
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nocardiosis as an Opportunistic Infection in COVID-19

Abstract: Secondary bacterial pneumonia infection is frequent in COVID-19 patients. Nocardia are responsible for opportunistic pulmonary infections especially after steroid treatment. We describe a case of pulmonary nocardiosis following critical COVID-19 pneumonia in an 83-year-old male. Two weeks after initiation of dexamethasone 6 mg/L, the patient developed a new episode of acute dyspnea. The sputum cultures identified Nocardia cyriacigeorgica. In spite of intravenous imipenem and cotrimoxazole treatment the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…With the rarity of Nocardia infections, there is a lack of formal guideline-directed treatment compared to other infections [ 2 ]. Although there are multiple studies and case reports published, there is a lack of clinical trials to determine optimal therapies and inconsistency with the in vitro and in vivo antibiotic susceptibilities [ 20 ]. Multiple studies reported treatment with sulfonamides, although antibiotic and anti-microbial susceptibility testing is recommended to identify specific Nocardia strains and determine susceptibility patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rarity of Nocardia infections, there is a lack of formal guideline-directed treatment compared to other infections [ 2 ]. Although there are multiple studies and case reports published, there is a lack of clinical trials to determine optimal therapies and inconsistency with the in vitro and in vivo antibiotic susceptibilities [ 20 ]. Multiple studies reported treatment with sulfonamides, although antibiotic and anti-microbial susceptibility testing is recommended to identify specific Nocardia strains and determine susceptibility patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reported treatment with sulfonamides, although antibiotic and anti-microbial susceptibility testing is recommended to identify specific Nocardia strains and determine susceptibility patterns. Various Nocardia species have different resistance patterns, particularly with commonly used TMP-SMX [ 20 ]. Consequently, antibiotic treatment is prolonged or relapse with disease progression has been described in certain cases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An English literature review showed only other five reports of these associations. Data regarding these cases are shown [6][7][8][9][10].…”
mentioning
confidence: 99%
“…[2][3][4] High dose TMP-SMX combined with meropenem successfully treated N. cyriacigeorgica in our patient and has been reported as sufficient therapy for nocardiosis in several case studies of adult patients with PCD and other airway diseases with impaired mucociliary clearance. [3][4][5][6][7] Finally, some questions remain. There is no data on the optimal length and dosage of a treatment course.…”
mentioning
confidence: 99%